Sociocultural factors influencing alcohol use among Korean immigrant women: A scoping review - Catherine Kim; Michael Butac; Hyoun S. Kim; Rosanra Yoon; Josephine Pui-Hing Wong (PLoS ONE, 2026)
Background Although studies of alcohol use have explored the experiences of various ethnocultural communities in diverse countries such as Canada, there is a noticeable gap in primary research concerning the experiences of Korean immigrant women. With alcohol consumption rising among women relative to men in recent decades, a critical understanding of existing knowledge on alcohol use through the lenses of culture and gender is essential. Research Question What is the current state of evidence on alcohol use among Korean immigrant women? Methods This scoping review was conducted using the five-stage framework adapted from Arksey and O’Malley (2005) and extended by Levac et al. (2010), with reporting guided by the Joanna Briggs Institute PRISMA-ScR framework. Inclusion criteria comprised primary studies focused on both Korean immigrant women and alcohol use, from Canada, the United States, the United Kingdom, Australia, and New Zealand, restricted to adult ages and English-language publications. Inductive thematic analysis as outlined by Gottlieb et al. (2021) was employed to extract themes from the included articles. Results Seven articles met the inclusion criteria, all from the United States, revealing no existing research on this topic from any other eligible country. Three major sociocultural themes influencing alcohol use were identified: acculturation, religion, and social networks. Additional contextual factors including immigration-related stress and traditional Korean drinking customs were noted as plausible but less consistently reported influences. Conclusions Findings underscore the importance of adopting culturally sensitive, gender-specific approaches in public health initiatives targeting alcohol use among Korean immigrant women. Substantial gaps remain, particularly regarding the Canadian context.